Deciphering the chemical dialogue between Bacillus and pathogenic fungi. - Pérez-Lorente, Alicia Isabel; Molina-Santiago, Carlos; Vela, David; Stincone, Paolo; Pakkir Shah, Abzer K.; De-Vicente-Moreno, Antonio; Petras, Daniel; Romero-Hinojosa, Diego Francisco (My University, 2024)
In nature, bacteria frequently form bacterial communities known as biofilms, where cells are embedded within an extracellular matrix (ECM) that provides protection against external aggressions or facilitates the efficient uptake and utilization of available resources. Interactions with other microbes can notably alter the community structure and, consequently, the nature of the relationship with the environment1. Previous studies of our laboratory have demonstrated the significance of biofilm formation in the antagonistic interaction between Bacillus and the phytopathogenic fungi Botrytis in the melon phyllosphere2. Our hypothesis is that the ECM plays a complementary role to the structural aspects of this antagonistic interaction. In this study, we dissect how the different components of Bacillus ECM mediate the adhesion of bacterial cells to Botrytis hyphae, which could enhance the efficient release of antifungal metabolites. We also describe how several purified components of the ECM and specific secondary metabolites of Bacillus participate in the chemical communication between Bacillus and Botrytis, thereby altering the physiology and metabolism of Botrytis. Our findings unveil that during this antagonistic interaction, Botrytis secrets different oxylipins, defence molecules capable of killing Bacillus. In response, Bacillus increases the production of several secondary metabolites, which appears to have antifungal effects. Our results underscore the urgency of further investigation of these interactions with the aim of identifying and describing adaptation processes that either lead to the exclusion or coexistence of two initially antagonistic microorganisms.
Keywords: Biopelículas; Ecología microbiana; Microbial interactions; Bacillus; Metabolomics